УПРОСТИТЕ ВЫРАЖЕНИЕ: a+b+c-(a-b-c)= 7(2a+5b)-5(3b-4a)= -2(a-3b)+3(b-2a)= ПРЕДСТАВЬТЕ В ВИДЕ СУММЫ ВЫРАЖЕНИЕ: 1)15a-9; 2)a-b-c 3)x-3y
УПРОСТИТЕ ВЫРАЖЕНИЕ:
a+b+c-(a-b-c)=
7(2a+5b)-5(3b-4a)=
-2(a-3b)+3(b-2a)=
ПРЕДСТАВЬТЕ В ВИДЕ СУММЫ ВЫРАЖЕНИЕ:
1)15a-9;
2)a-b-c
3)x-3y
Ответ(ы) на вопрос:
1. a+b+c - (a-b-c) = a+b+c-a+b+c = 2b + 2c + 0a
2. 7(2a+5b) - 5(3b-4a) = 14a + 35b - 15b + 20a = 34a + 20b
3. -2(a-3b) + 3(b-2a) = -2a + 6b + 3b - 6a = -8a + 9b
1. 15a+9
2. a+b+c
3. x+3y
Не нашли ответ?
Похожие вопросы